Increasing access and reducing operational unit cost in public secondary schools in Edo State, Nigeria (2012)
The problem of increasing financial burden of education in the face of other pressing macroeconomic needs poses serious challenges to educational development in Nigeria. Moreover, there is an increasing demand for education at a time when government revenues are dwindling. This problem compounded by the inefficient use of available resources in schools. This has resulted in a high cost of public school operation. This has necessitated the need to explore alternative means of improving control over the cost of education and increase access to public schools. This study, therefore investigated the influence of a number of size factors (enrolment, average class size and student-teacher ratio) on the operational unit cost of public secondary schools in Edo Stale. Nigeria. The study adopted the descriptive survey research design of ex-post facto type. Multistage sampling techniques were used to select 207 out of the total of 509 conventional public secondary school across the three senatorial districts of Edo State. Two inventories were used to generate secondary data from the selected schools and two State Ministry of Education officials. The school inventory was used to obtain data on individual school size features and recurrent expenditures while the inventory for Ministry of Education was used to collect aggregate school enrolment, class, staff and recurrent expenditures in the state during the research period. Three research questions were answered and data analysed using descriptive statistics. The results showed that increasing the various size factors invariable reduces operational unit cost of schooling and hence, generated monetary savings for the school System in the state. Notably the results indicated that the reduction in unit cost is not linear, implying that cost reduced at a declining rates. Therefore, enrolment average class size and student-teacher ratio could be increased to a permissible level as a cost reduction strategy in public schools